Germline variation at 8q24 and prostate cancer risk in men of European ancestry - Matejcic, Marco; Brenner, Hermann (Nature Communications, 2018)
Chromosome 8q24 is a susceptibility locus for multiple cancers, including prostate cancer. Here we combine genetic data across the 8q24 susceptibility region from 71,535 prostate cancer cases and 52,935 controls of European ancestry to define the overall contribution of germline variation at 8q24 to prostate cancer risk. We identify 12 independent risk signals for prostate cancer (p < 4.28 × 10−15), including three risk variants that have yet to be reported. From a polygenic risk score (PRS) model, derived to assess the cumulative effect of risk variants at 8q24, men in the top 1% of the PRS have a 4-fold (95%CI = 3.62-4.40) greater risk compared to the population average. These 12 variants account for ~25% of what can be currently explained of the familial risk of prostate cancer by known genetic risk factors. These findings highlight the overwhelming contribution of germline variation at 8q24 on prostate cancer risk which has implications for population risk stratification., Chromosome 8q24 is known to be a major susceptibility region for prostate cancer risk. Here the authors analyze genetic data across the 8q24 region from 71,535 prostate cancer patients identifying 12 risk loci, three previously unreported, highlighting the contribution of germline variation at this locus.
Gesehen am 19.12.2018